MODEL AIDA SEBAGAI STRATEGI PEMASARAN BANK SYARIAH DI MASA PANDEMI COVID-19 (STUDI MASYARAKAT INDRALAYA) - Melati (LA RIBA: Jurnal Perbankan Syariah, 2020)
The purpose of this research is to analyze AIDA's marketing model strategy at the Syariah bank during the Covid-19 pandemic. This study used descriptive qualitative method. Interviews were conducted on informants who are the marketing team and customers of Syariah Bank. The result of this research is that Mandiri Syariah Bank uses the AIDA model as a marketing strategy during the pandemic, namely the first way of Attention, which is to attract attention or attention, in a pandemic Islamic banks do marketing by means of digital banking, making brochures, advertising on the internet and digital banking. Second, build interest, namely by giving a good first impression and providing assistance and consultation to customers online and offline. Third, Desire by means of learning classes there, the customers will be introduced to Islamic banking products using media zoom tools and credit guarantee levers in the field or OTS via video call or zoom. The fourth actioan with what has been marketed before is based on sharia principles where the system does not use usury but uses a profit sharing system.